PBL and Sociolinguistics - Engku Ibrahim, Engku Haliza (2006)
The objective of this paper is to report on an action research carried out to stimulate active learning in the teaching of an introductory Sociolinguistics course to undergraduates. It is common to hear lecturers complaint of passive learners who expect to be spoon-fed in their courses. The aim of this research is to persuade and challenge undergraduate students to play an active role in their own learning process. This paper illustrates the strategies adopted and reports on the feedback from students at the end of the semester.